An efficient and weak efficiency-roll-off near-infrared (NIR) polymer light-emitting diode (PLED) based on a PVK-supported Zn2+–Yb3+-containing metallopolymer. Issue 15 (28th March 2018) - Fu, Guorui; Guan, Jiaqing; Li, Baoning; Liu, Lin; He, Yani; Yu, Chao; Zhang, Zhao; Lü, Xingqiang
Abstract : Based on the Zn 2+ –Yb 3+ -containing metallopolymerPoly(NVK- co -3) (75 : 1), PLEDs I–II with or without TPBI exhibit a record-renewed performance (80.14–85.63 μW cm −2, 0.05–0.058%, and weaker efficiency-roll-off) relative to Yb 3+ -doped PLEDs. Abstract : Based on copolymerization of NVK ( N -vinylcarbazole) with an efficient Yb 3+ -centered NIR luminescent complex monomer [Zn(L 1 )(4-vinyl-Py)Yb(L 2 )3 ] (3 ) (H2 L 1 = N, N ′-bis(salicylidene)cyclohexane-1, 2-diamine, 4-vinyl-Py = 4-vinyl-pyridine, andHL 2 = ( Z )-3-methyl-1-phenyl-4-(2, 2, 2-trifluoro-1-hydroxyethylidene)-1 H -pyrazol-5(4 H )-one), the obtained single Zn 2+ –Yb 3+ -containing metallopolymerPoly(NVK- co -3) with an additional PVK (poly( N -vinylcarbazole))-to-Yb 3+ Föster energy transfer was used as the emitting layer for the realization of NIR PLEDs. Moreover, among the Yb 3+ -centered NIR PLEDs, the superior performance (irradiances of 80.14–85.63 μW cm −2 and efficiencies of 0.05–0.058%) of the 75 : 1 feeding devices, the advantages of a low turn-on voltage (5–8 V), and the weak efficiency-roll-off relative to that of the small-molecule organo-Yb 3+ -based NIR OLEDs render the Yb 3+ -containing metallopolymer a new platform for PLEDs with wavelength above 900 nm.